Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1128/aem.01958-06
|View full text |Cite
|
Sign up to set email alerts
|

Development and Evaluation of Methods To Detect Nucleopolyhedroviruses in Larvae of the Douglas-Fir Tussock Moth, Orgyia pseudotsugata (McDunnough)

Abstract: Various molecular methods are used to detect pathogenic microorganisms and viruses within their hosts, but these methods are rarely validated by direct comparison. Southern hybridization, enzyme-linked immunosorbent assay (ELISA), and a novel DNA extraction/PCR assay were used to detect Orgyia pseudotsugata multiple nucleopolyhedrovirus (OpMNPV) in Douglas-fir tussock moth larvae. PCR was more sensitive than Southern hybridization and ELISA at detecting semipurified virus. ELISA, however, was the most accurate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Sodium dodecyl sulphate (SDS) is an anionic surfactant capable of disrupting non-covalent bonding in proteins and denaturing them with most proteins that lose their functions completely or partially in its presence (Yamada et al, 1998). In insect pathological works, SDS has been used routinely for extracting and purifying baculovirus polyhedra from infected cells of diseased insects for bioassays (Thorne et al, 2007). The compound lyses cells and expose the DNA.…”
Section: Introductionmentioning
confidence: 99%
“…Sodium dodecyl sulphate (SDS) is an anionic surfactant capable of disrupting non-covalent bonding in proteins and denaturing them with most proteins that lose their functions completely or partially in its presence (Yamada et al, 1998). In insect pathological works, SDS has been used routinely for extracting and purifying baculovirus polyhedra from infected cells of diseased insects for bioassays (Thorne et al, 2007). The compound lyses cells and expose the DNA.…”
Section: Introductionmentioning
confidence: 99%
“…Like most animals, insects are susceptible to diseases caused by viruses, and many viruses have been applied as insecticides (Tweeten et al 1981;Moscardi 1999). In the United States, Nuclear polyhedrosis viruses (NPVs) are used as insecticides (Thorne et al 2007). The NPVs suppress the corn earworm moth (Heliothis zea), the Asian gypsy moth (Lymantria dispar), and the Douglas fir tussock moth (Orgria pseudotsugata) (Shieh & Bohmfalk 1980).…”
mentioning
confidence: 99%
“…The detection range of samples obtained in this study (over 5 £ 10 4 OBs6 mL) is within the range reported by other authors for immunological techniques such as ELISA. For instance, Parola et al (2003) and Thorne et al (2007), using baculovirus as an antigen, were able to develop antibodies for the detection of granulovirus from insect larvae and complex samples of granulovirus formulations.…”
Section: Affinity Of the Selected Antibodies For The Viral Antigenmentioning
confidence: 99%